MEKANISME PENETAPAN IURAN PENGELOLAAN LINGKUNGAN: Mechanism For Determining Management Fees In Flat Houses - Cahya Mahasura; Anda Setiawati (Faculty of Law, Universitas Trisakti, 2025)
The issue of Environmental Management Fee (IPL) often causes disputes that lead to lawsuits in court. To determine the amount of IPL, it is necessary to know how the mechanism is. The formulation of the problem in this study is how the mechanism for determining IPL in flats. Studies related to this matter are carried out using normative legal research methods sourced from secondary data or library data. Based on PP No. 13/2021 and Permen PUPUR No. 14/2021. The results of the discussion and conclusion are that based on PP No. 13/2021 and PUPR Regulation No. 14/2021, the determination of IPL is based on the bylaws and general meeting of PPPSRS members. Specifically for flats in the Jakarta area, the provisions of DKI Governor Regulation No. 132/2018, which has been amended by Governor Regulation No. 70/2021, also apply, which stipulates that the IPL determination mechanism is based on bylaws and general meetings with reference to the voting rights of owners and residents based on the Proportional Comparison Value (NPP).